Ammonia Volatilization in Cocoa Farm as Affected by Sugarcane Filter Cake Supply at Different Urea and Soil Moisture Levels - Erwin Prastowo; Nadya Faiqotul Hikmah; John Bako Baon (Indonesian Coffee and Cocoa Research Institute, 2014)
Ammonia (NH3) volatilization is a crucial mechanism in soil nitrogen (N) cycle. It accounts for main loss of N in cocoa farms when environment is suitable to promote the emission. A research to locate a link of several factors, namely, sugarcane filter cake (SFC), urea and soil moisture content to NH 3 volatilization, and to reveal cocoa N uptake and urea fertilizer efficiency was taken place both in a laboratory with the incubation technique, and in a greenhouse as a pot trial. The design was completely randomized design in factorial. The soil was Inceptisol from Kaliwining Experimental Station, Jember, East Java, collected from top soil of a productive cocoa farm. A closed trap system was designed to measurevolatilized NH 3 from soil and SFC mixture incubated for 14 days. For the pot experiment, cocoa clone of Scavina 6 seedlings were grown for six months withtreatments involving series level of SFC and series level of urea. Soil moisture content influenced volatilized NH3 by reducing 50% emission in where it was more obvious in higher level of urea applied. It was more than 90% in average for the increase in volatilized NH 3roduced by increasing in level of urea from 0 to 0.4 g kg -1 in overall level of combinations. An increase in urea level had resulted in increase in soil pH, and Parson correlation suggested a direct link with volatilized NH 3 We found a relationship between SFC and volatilized NH 3 and their combinations with soil moisture and urea content were able to inhibit the emission. Emission decrease up to 28% was observed from 0 to 100 g SFC kg-1. This inhibition may have contributed to the increase in N cocoa plant uptake by more than 70% compared to control and subsequent increase in N fertilizer supply efficiency up to 86% in the combination with 0.2 g urea kg-1. The absence of SFC had made a decline in urea efficiency about 20 times.Keywords: ammonia volatilization, sugarcane filter cake, urea, soil moisture, cocoa